CCAFS Climate Smart Villages project in South Asia: An Introduction - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) has introduced the model of "Climate Smart Villages (CSVs)" in India, and is slowly scaling up and expanding to other countries in the South Asia region. www.ccafs.cgiar.org The idea is to raise awareness among farming communities in South Asia about various technological, institutional and policy-oriented options that have the potential to increase their climatic resilience, adaptation, agricultural productivity and income, while reducing emissions of greenhouse gases. Interventions that were made, relate to: weather, water, carbon, nutrient, energy and knowledge management. Read more: http://ow.ly/kXVFR